AI-Powered Platforms for Interactive Nutrition Education Based on WHO (World Health Organization) Guidelines – An Overview - Taiwo Folake Ojo; Oluwaseyi Abiodun Akpor; Yetunde Justinah Talabi; Adeniran Sunday Afolalu (ABUAD Journal of Engineering Research and Development)
Malnutrition is still a major worldwide health issue; hence creative methods of nutrition teaching are required. The transformational potential of artificial intelligence (AI)-powered platforms to provide individualized and interactive nutrition education in line with World Health Organization (WHO) guidelines is examined in this paper. It explores how AI improves engagement through gamification and virtual coaching, makes tailored dietary suggestions based on individual needs and tastes, and offers data-driven feedback for tracking success. The study looks at how well these platforms match WHO nutritional guidelines and considers the advantages—like higher engagement and better memory retention—as well as the drawbacks—like data privacy, algorithmic bias, and unequal access. Additionally, it investigates how AI improves user engagement through interactive features like gamification, chatbots that employ natural language processing to provide individualized virtual coaching, and dynamic feedback systems for behavior reinforcement and progress monitoring. To show how these AI-driven platforms can encourage adherence to evidence-based guidelines for balanced diets, appropriate nutrient intake, and the prevention of diet-related non-communicable diseases, the report explores the critical alignment of these platforms with specific WHO dietary recommendations. This study critically examines the associated challenges, including worries about data privacy and security, the possibility of algorithmic bias, the need for fairness and equity in AI-driven recommendations, and the crucial issue of ensuring equitable access to these technologies across diverse populations, addressing the digital divide, in addition to the advantages of increased user engagement and improved knowledge retention